Hubungan Peak Left Atrial Longitudinal Strain dengan Derajat Keparahan Penyakit Jantung Katup Mitral di RSUP Haji Adam Malik Medan - Ryanti, Dina; Ketaren, Andre Pasha; Mukhtar, Zulfikri; Akbar, Nizam Zikri; Lubis, Anggia Chairuddin; Ardini, Tengku Winda (The Indonesian Heart Association, 2023)
Introduction: Mitral stenosis and regurgitation, are common throughout the world. Peak Left Atrial Strain (PALS) is a parameter for assessing left atrial deformation in the evaluation of atrial function and a predictor of long-term outcome of various heart diseases. In this study, we assessed the relationship between PALS and the severity of mitral stenosis and mitral regurgitation Methods: This is a cross-sectional study on 119 subjects with mitral stenosis and 103 mitral regurgitation who met the inclusion criteria at Haji Adam Malik General Hospital. PALS measurements were taken. Data were analyzed univariate, bivariate, correlate to assess the relationship between PALS and the severity of mitral valve disease Results: 119 patients with severe mitral stenosis. In mitral stenosis, the mean PALS is 8.2 (4.9-22.8). PALS was significantly higher in patients with sinus rhythm than in the group with AF (10.29 ± 3.89 vs 8.63 ± 7.8%; P = 0.002). PALS had a significant correlation with MVA, pressure gradient, and PHT (r = 0.676, P = <0.001; r=-0.594, P= 0.001 and r=-0.594, P= 0.001). Whereas in mitral regurgitation, it has an average PALS of 15.2 (7.8-19.2). PALS was also significantly higher in patients with sinus rhythm than in the group with AF (16.36 ± 2.43 vs 11.64 ± 2.89%, P = 0.001). PALS has a correlation with VC, PISA, EROA and RVol (r = -0.533, P=0.001; r=-0.618; r=-0.563, P=0.001; r= -0.528, P=0.001). Conclusion: PALS has a significant correlation with the assessment of the severity of mitral stenosis and regurgitation.This articles has a related Erratum.